2021
DOI: 10.17770/etr2021vol3.6627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the High-Speed Flow of Powder Particles on the Structure of Polymer Materials and Metal-Polymer Composites

Abstract: The problem of protecting spacecraft from cosmic dust has recently come to the fore. There is still no enough data on the complex effect of short-term high-energy, dynamic loading on materials, including polymer materials and multilayer polymer-metal composites. The use of dynamic alloying in the super-deep penetration (SDP) mode by high-speed flows of powder particles allows assessing the effect on the material under dynamic action. Previous studies on steel and aluminum samples have shown a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It showed that they possessed higher efficiency than solid shields. It was found in the research [60][61][62] that the resistance of such screens can be increased due to various geometric features of their components (mutual arrangement of layers, angle of inclination, etc. ), as well as from the materials of the layers and their order.…”
Section: Metal Screens From the Waste Of Perforated Sheetsmentioning
confidence: 99%
“…It showed that they possessed higher efficiency than solid shields. It was found in the research [60][61][62] that the resistance of such screens can be increased due to various geometric features of their components (mutual arrangement of layers, angle of inclination, etc. ), as well as from the materials of the layers and their order.…”
Section: Metal Screens From the Waste Of Perforated Sheetsmentioning
confidence: 99%